Increasing the Life of Mulching Tools - Ľuptáčiková, Veronika; Hnilica, Richard; Ťavodová, Miroslava (International Journal of Engineering and Management Sciences, 2019)
Areas after mining or calamity are not amenable to immediate afforestation and require some adjustment. After removal of wood biomass, the rest of the residue is scattered throughout the area. To modify them, Several methods can be used to remove it. The optimal conditions for the planting environment and the subsequent adaptation process of the planting can be achieved by its mechanical, biological, chemical treatment. The basic prerequisite for a successful renewal of forests is their release from undesirable increases, in some cases from foams (trees) from mining waste. The area is also released when forest nurseries, seed plantations, etc. are established. The main purpose of the release of surfaces is to achieve the maximum throughput of the area for the machines to be moved. They wear during work. Wearing is a permanently undesirable change in the surface due to the interaction of functional surfaces or functional surface and wear medium. A tool that does not have any editing can go into a state where it can no longer be used anymore. An experiment was carried out in which 9 new teeth were placed on the rotor of the crusher and their wear patterns were observed. The article shows the progress of tool wear over time.